(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
The changes of statistical characteristics of heart rhythm during carrying out of maze-model tasks on the computer are investigated. Two groups of probationers were allotted by their reaction to the loading: the first group is characterized by the decreasing of strain index (SI); the second group – by the increasing of SI. It is shown, that at the most of probationers, carrying out the tasks with high efficiency, the heart rhythm regulation is realized by the level of autonomous contour, while at the most of probationers carrying out the tasks with low efficiency – by the level of central contour.